Answer:
x = 1.13
Step-by-step explanation:
Answer:
36
Step-by-step explanation:
3/4y=6-1/3c
3/4y+1/3c=6
multiplied 6 into equation to get 2c
9/2y+2c=36
so 2c+9/2y=36
Rmember (a/b)/(c/d)=(a/b)(d/c)=(ad)/(bc)this is just alot of busy work
find f+g first then find f-g
f+g=(x-4)/(x+9)+(x-9)/(x+4)
make denomenator the same
multiply left one by (x+4)/(x+4) and right one by (x+9)/(x+9)
[(x-4)(x+4)]/[(x+9)(x+4)]+[(x-9)(x+9)]/[(x+9)(x+4)]
[x²-16]/[(x+9)(x+4)]+[x²-81]/[(x+9)(x+4)]
[x²+x²-16-81]/[(x+9)(x+4)]
[2x²-97]/[(x+9)(x+4)]
now f-g
[x²-16]/[(x+9)(x+4)]-[x²-81]/[(x+9)(x+4)]
[x²-x²-16+81]/[(x+9)(x+4)]
[65]/[(x+9)(x+4)]
now we got
![\frac{ \frac{2x^2-97}{(x+9)(x+4)} }{ \frac{65}{(x+9)(x+4)} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%5Cfrac%7B2x%5E2-97%7D%7B%28x%2B9%29%28x%2B4%29%7D%20%7D%7B%20%5Cfrac%7B65%7D%7B%28x%2B9%29%28x%2B4%29%7D%20%7D%20)
invert and multiply
![(\frac{2x^2-97}{(x+9)(x+4)})(\frac{(x+9)(x+4)}{65})](https://tex.z-dn.net/?f=%28%5Cfrac%7B2x%5E2-97%7D%7B%28x%2B9%29%28x%2B4%29%7D%29%28%5Cfrac%7B%28x%2B9%29%28x%2B4%29%7D%7B65%7D%29)
![\frac{2x^2-97}{65}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%5E2-97%7D%7B65%7D%20)
2nd option
<span>11.00001 - 1.11234</span> = 9.88767
The formula for the area of a trapezoid is:
A= (a+b)/2*h
A=150
h=10
b=14
a=?
So we need to solve for a. Let's plug in the values that we do know...
A= (a+b)/2*h
150=(a+14)/2*10
150=(a/2+14/2)*10
150=(a/2+7)*10
Divide both sides by 10
15=a/2+7
subtract 7 from both sides
8=a/2
multiply both sides by 2
16=a
The other base is 16